Integrating Enterprise Architecture into Intelligent Transportation System: A Step Towards Sustainable Mobility - Andriangsih, Andriangsih; Sani, Asrul; Firmansyah, Mochamad (IWJ : Inland Waterways Journal, 2023)
As a strategic step toward sustainable mobility, this study examines the integration of Enterprise Architecture (EA) into an Intelligent Transportation System (ITS) utilizing the TOGAF framework (The Open Group Architecture Framework). Given the escalating intricacy of the transportation system, the primary emphasis is on the synergy between ITS and EA, which is organized and structured using TOGAF. This study aims to determine how the TOGAF framework can aid in developing a more sustainable and efficient transportation system by facilitating the integration of EA and ITS. This methodology is grounded in qualitative analysis, particularly an exhaustive review of the relevant literature. This literature review identifies current trends and best practices regarding applying TOGAF for EA integration in ITS. Research shows that transportation service operational efficiency and effectiveness are enhanced when EA and ITS are integrated using TOGAF, improving coordination, resource management, and strategic decision-making. This, in turn, supports sustainable mobility.